치과위생사의 임파워먼트와 조직몰입의 관계 - 이혜경; 김미정; 임연실 (Han'guk Ch'iwisaeng Hakhoe chi, 2010)
Objective : This study provides dental care organization that is responsible for services of dental hygienists to measure levels of empowerment and organizational commitment to. The impact of empowerment on organizational commitment is a variable that has to validate the improvement of organizational commitment of dental hygienists to have been studied for the suggestions. The study period 2009 July 1 to August 30 at Jeonju Jeollabuk dental material and dental hygienists are working in medical institutions to target a total of 336 copies (88.4%) and for analysis of the data was studied. Methods : For data analysis SPSS (Statistial Package for the Social Science) WIN 12.0 program using frequency analysis, T-test and One-way ANOVA test, Pearson's correlation coefficient, linear regression analysis was conducted through the following. Results : 1. Demographic characteristics (education, salary, age, workplace), the empowerment and organizational commitment as the decisive factor affecting the level was a significant difference. 2. Education, salary, age and demographic characteristics of the working period of the empowerment uimiseong, yeokryangseong, self-determination, but no significant differences in impacts factors, work factors, not only was a significant difference uimiseong. 3. Demographic characteristics (education, salary, age, duration of employment, workplace), the affective commitment, normative commitment, ever, ever commitment and showed significant differences remain. 4. The higher the level of empowerment of the subjects that were higher organizational commitment, was a significant difference. 5. Empowerment and Organizational Commitment of subjects related factors were analyzed in all the variables showed a significant correlation between. Conclusions : Dental health agencies that provide services of dental hygienists to improve empowerment and organizational commitment to develop a structured management program, a dental hygienist job dental hygienist program and professional standards for the continuous and systematic research. That will be needed. KCI Citation Count: 18